POTENSI DAUN PEPAYA (CARICA PAPAYA L) SEBAGAI ALTERNATIF MEMPERLANCAR PRODUKSI ASI - Istika Dwi Kusumaningrum (STIKes Surya Global Yogyakarta, 2017)
Background: The community is more like traditional medicine to facilitate breastfeeding than drugs, such as herbal medicine. But not a few also mothers who like drugs because it is easier and faster. Keep in mind if taking herbs in the form of extracts and packaging need to be considered also the ingredients. Method: This research used experimental method by using papaya leaf with paste and giving uyupuyup herbal medicine. In this experiment using two groups of treatment groups that were affixed papaya leaves and herbal medicine uyup-uyup papaya leaves. The population in this study were all mothers who had babies / toddlers who were still breastfeeding. Sampling method in this research was non-probilitiy sampling technique that was purposive sampling where sampling based on criterion of researcher. So the number of samples taken for the research were many as 30 people. The research was begun by determining the study respondents. Then the respondents measured the production of breast milk pre-test. After that giving papaya leaf to the respondent, then the researcher gave post-test to the respondent to know milk production. Result: Based on statistical test result with SPSS obtained Correlation result = 0,994 and Sig. = 0,000 where p 0.05, it showed that there were differences in the composition of breast feeding in pre-test group and post-test group or it can be said there was significant influence after papaya leaf attachment to the smoothness of milk production. Giving papaya leaf by drinking herbs uyup-uyup papaya leaf more effective than papaya leaf patching only, proved from the results of statistical tests on the 5.5 mark stated the amount of Mean for the treatment of papaya leaf attachment of 2.93 while the treatment of herbal medicine uyup-uyup papaya leaf 27.17, so it can be said herbal medicine uyup-uyup papaya leaf more effective.